Autoestima y rendimiento académico en los adolescentes - Castillo Daza, Ana Rosa , Flores Valderrama, Rosa Elena (2019)
The purpose of this research has been to determine the relationship between the selfesteem and the academic performance of the adolescent students of the “San Nicolás” Educational Institution in the district of Huamachuco, Province of Sánchez Carrión, Department of La Libertad. This research of quantitative design, descriptive and crosssectional method with a sample of 104 adolescent students belonging to the 4th and 5th grade of secondary education of sections "A" and "B"; which were randomly selected. For data collection, the instruments of the Coopersmith Modified Self-Esteem Scale and the Official Record of Notes were used; and measure the variables to make the corresponding correlations and comparisons, the reliability of the instrument was determined through the Cronbach Alpha statistical test resulting in: 0.835. The instrument is considered reliable. The results indicate a good reliability and internal consistency of the instruments; The relationship between both variables was determined by Pearson's correlation, with a level of significance of 0.01. The data processing was performed using the statistical package IBM SPSS STADISTIC version 23. The results were reported in tables of distribution of onedimensional frequencies with their absolute and relative percentage values, with a 95% confidence level concluding that: there is a significant relationship between teenagers' selfesteem and academic performance.